Paroxysmal Nocturnal Haemoglobinuria - An Atypical Presentation (Journal of Medicine, 2019)
Paroxysmal Nocturnal Haemoglobinuria (PNH) is a rare, acquired disorder of haemopoitic stem cell, characterized by abnormal sensitivity of red cells to haemolytic action of complement leading to intravascular haemolysis. Though PNH typically presents as nocturnal haemoglobinuria, however presentation varies as for example bicytopenia, aplastic anaemia or repeated venous thrombosis. One such atypical presentation was seen in 35 years old male who presented with the history of generalized weakness, fever and oral ulceration. The PNH was diagnosed by flow cytometric analysis of GPI linked protein and associated laboratory features of chronic haemolysis. We report this case to create awareness about the fact that PNH can present without haemoglobinuria.J MEDICINE JUL 2019; 20 (1) : 46-48